Electrochemical techniques used to study bacterial-metal sulfides interactions in acidic environments - Bevilaqua, Denise [UNESP]; Acciari, Heloisa A. [UNESP]; Benedetti, Assis V. [UNESP]; Garcia Jr., Oswaldo [UNESP] (Springer Nature, 2007)
Bioleaching or bacterial leaching is a dissolution process of metal sulfides in which the oxidative activity of some bacterial species, mainly Acidithiobacillus ferrooxidans, formerly Thiobacillus ferrooxidans (Kelly &Wood, 2000), plays a central role. As a consequence of its capacity, this bacterium is one of the most important microorganisms utilized in industrial operations to recover metals, such as copper, uranium and gold (Rawlings, 2002). This chemolithotrophic and acidophilic species utilizes ferrous iron or metallic sulfides as the sole energy source for CO2 fixation and its growth, according to the following equations: (1) 4FeSO4+O 2+2H2SO4→2Fe2(SO 4)3+2H2O (2) MeS+2O2→MeSO 4 where Me is the metal of interest. This species can also oxidize other reduced forms of sulfur to produce energy according to the equations: (3) 2S+3O2+2H2O→2H2SO4 (4) Na 2S2O3+2O2+H2O→ Na2SO4+H2SO4 The biological mechanisms and the reactions that come into play during the oxidative dissolution of metal sulfides by bacterium are controversial and still poorly understood with different authors suggesting that its presence enhances leaching, has no effect or is detrimental to the metal leaching (Third et al., 2000; Tributsch, 2001). The knowledge of the mechanisms of bacterial dissolution of sulfides has been focused in several copper minerals, in order to improve the efficiency of the bioleaching operations. The oxidation of sulfides by a chemical or biological oxidant can be look upon as an electrochemical reaction with the cathodic reduction of the oxidizing agent (bacterial cell, for example) and the anodic oxidation of the reducing one (metal sulfide), and it can consequently be studied by electrochemical techniques. Electrochemical studies of mineral sulfide dissolution in acid oxidizing solutions (bacterially produced or not) are powerful tools to elucidate mechanisms and kinetics of these reactions. The mineral oxidative dissolution is a corrosion reaction, with anodic and cathodic half-reactions, which in oxidizing media such as acidic ferric chloride or sulfate solutions is very slow. Therefore, mechanistic studies were proposed in order to explain this slow rate, especially from the viewpoint of the anodic process (Biegler &Horne, 1985; Gómez et al., 1997; Gómez et al., 1996; Pesic &Kim, 1990). In these studies the following aspects were considered: • Influence of temperature; • Addition of ferrous or ferric ions in sulfate medium; • Addition of catalytic cation; • Origin of the mineral sample; • Effect of applied potential; • Influence of pH. As a general result of these studies it was observed the presence of passive layer that limits the oxidation rate of the mineral sulfide in the medium. Although the composition of this layer was not well characterized yet, it has been described as: • Metal-deficient sulfide; • Polysulfide; • Solid electrolyte interphase; • Precipitated iron compounds. Its effect on the oxidation kinetics has been explained in terms of physical blockage, solid-state diffusion of metal ions and passive film growth. Voltammetric studies complemented with XPS analysis demonstrated that in acidic solutions the surfaces of bornite and chalcopyrite are covered with a CuS layer which is formed according to the following reactions (Kudaikulova, 1989): (5) CuFeS2+2H+→ CuS+Fe3++H2S+e-(6) 2Cu2S+2H2S→ 4CuS+4H++4e-In solutions of pH>4 a film of copper oxide and iron hydroxide is formed on the bornite surface which protects the mineral against further oxidation. In the late 1980s, the electrochemical oxidation of natural mineral sulfide electrodes in the presence or absence of bacteria in sulfuric acid medium was studied for several authors using both voltammetric and chronoamperometric techniques, at different experimental conditions, using mineral massive or carbon paste electrodes (Biegler &Horne, 1985; Kudaikulova, 1989). In the early 1990s the works on carbon paste electrodes (CPE) modified with mineral sulfides emerged in the electrochemistry field. The physical state of the mineral in the CPE electrodes is similar to that in industrial leaching processes; for this reason, the use of CPE is closer to the real leaching conditions (Lázaro et al., 1995; Rodríguez et al., 2003; Lu, 2000; Elsherief, 2002). Lázaro and co-workers (1995) showed the reproducibility of the voltammetric response of CPE-chalcopyrite electrodes, as well as the differences in the kinetics of the leaching process in different acidic media. The voltammetric response is associated with chalcopyrite reduction to bornite and chalcocite. However, the CPE are not always sensitive enough because they involve small quantities of mineral embedded in the paste, which is not necessarily representative of the diversity of mineral grains. Another alternative is the use of Fixed Grains Electrode (FGE) that consists of ground mineral sulfide disperses on carbon paste previously prepared (Toniazzo et al., 1999). In recent years the voltammetric studies were utilized to characterize the products formed and their adhesion on mineral surfaces. An alternative for this study was to evaluate the anodic dissolution of chalcopyrite in acidic solutions and products formed using ring-disc electrode (RRDE) experiments. The oxidation-reduction reactions of metal sulfides are also susceptible to stirring that can be achieved by air bubbling (Holliday &Richmond, 1990). The chalcopyrite was also studied in alkaline solutions in order to characterize corrosion products formed on mineral surface. Yin and co-workers (2000) investigated the surface oxidation of chalcopyrite in alkaline solutions using chronoamperometry. The current-time transient was recorded in a 0.1 M borax solution, stepping to various positive potentials from a rest potential, in the range of predicted CuFeS2 thermodynamic stability. The integrated form of these data when plotted as Q against t-0.5 indicated that oxidation charge increased linearly with t-0.5 and the current decayed linearly with t-0.5. Such behavior, independent of solution stirring suggests that the oxidation process was controlled by solid-state mass transport, i.e. Fe3+ ion transport from the bulk of the chalcopyrite through the passive film up to reach the solid/electrolyte interface. Velásquez and co-workers (1998) evaluated the application of EIS to a chalcopyrite electrode in alkaline solution of borate (pH 9.2) to determine the influence of applied potential on the behavior of electrode/electrolyte interface and the equivalent circuit for modeling the electrode/solution interface. The authors concluded that the existence of a surface layer modified the double layer capacitance, which was associated with the mobile species in the surface layer. On the mineral surfaces several electrochemical processes can modify the surface to such an extension that it can be considered as a heterogeneous film of modified mineral, which is quite different from the substrate (Velásquez et al., 2000, 2001). In the last ten years a new concern has been raising up in the bacterial dissolution of sulfides, that is the importance of the exopolymeric substances (EPS) present in cell envelope and its role in the bacterial adhesion. However, this remains as a controversial topic, since the EPS can promote or inhibit the dissolution of mineral sulfides. Its formation and composition depend on the mineral characteristics, culture medium and bacterial species (Keresztes et al., 2001; Beech et al., 2002; Bevilaqua et al., 2004). Nowadays, the electrochemical impedance spectroscopy and electrochemical noise analysis are utilized for the same purpose, with emphasis in the proposition of models that explain the adhesion of the passive film or biofilm on mineral substrate. Details of each technique and some applications to the bacterial oxidative dissolution of mineral sulfides are presented in the next sections of this chapter. © 2007 Springer.